Philosophical Ideas of Gregory of Narek Regarding the Continuous Self-Improvement of Man - Manukyan, Ashot (Տիգրան Մեծ)
This report is an attempt to reveal the humanistic concept of human self-improvement developed by the 11th century Armenian philosopher, poet, songwriter, and Christian priest, Saint Grigor Narekatsi, canonized by the Catholic Church. The philosophical ideas of a Christian clergyman with a religious worldview regarding the relationship between the human soul, man and society, and man and God are revealed. In his poem ―The Book of Lamentations ―, the way of realizing the human dream of reaching divine perfection is discussed from the point of view of religious philosophy. His ecological views on the harmonious relationship between rational living matter, man, and nature deserve special attention. It is widely accepted that the psychoanalytical experience of Grigor Narekatsi enriched the universal word culture. From this point of view, Grigor Narekatsi‘s multifaceted spiritual legacy has not yet been studied and needs further research.
Keywords: Religious philosophy